Teachers' Hardiness Personality Towards Learning Dynamics In The Covid-19 Pandemic Period At Public Elementary School In City And District Of Kediri - Dyah Ayu Kartika Wulan Sari; Vitaria Wahyu Astuti; Erva Elli Kristanti (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
The main problems faced by teachers facing changes in learning dynamics include schools being transferred to homes through online and blended learning processes, transformation of technology-based learning media and learning adjustments and demands for collaboration between parents and students at home as a substitute for teachers controlling student learning. This sudden change also raises various new problems such as causing work stress. The purpose was to analyze the personality description of teacher’s hardiness towards learning dynamics during the Covid-19 pandemic at public elementary schools in city and district of Kediri. This research was conducted at SDN Setonorejo I,2, SDN Ngronggo 3 and SDN Burengan 2, Kediri City. This research used a descriptive analytical research design. The samples were all teachers at SDN Setonorejo I, SDN Sukorame 2, SDN Ngronggo 3 and SDN Burengan 2 who met the inclusion criteria with total sample of 50 respondents. The sampling technique used purposive sampling. The results showed that 47 respondents (94%) had good hardiness personality. It can be concluded that while facing changes in the learning dynamics, the teacher has developed a good coping mechanism so as to foster a high and resilient hardiness personality in dealing with stressors in learning dynamics. The results of this study are expected to be able to support the nursing profession to better participate in preventing work stress and improve the Hardiness Personality of education personnel, especially Elementary School Teachers.